The rise. 1972 - Castrovilla, Selene, 1966- (New York : Franklin Watts, an imprint of Scholastic Inc., 2023)
Explores the key events of the Civil Rights Movement, focusing on the year 1972, including the National Black Political Convention, Shirley Chisolm, and more.
Introduction: The Way It Was -- Unbought and unbossed -- Coming together for change -- Equality within reach -- Spring reckoning -- A hot time -- Broken promises -- Conclusion: The Legacy of 1972 in Civil Rights History -- Biography: Kristen Clarke -- Timeline.
School Library Journal, April 2023
Includes bibliographical references (page 92) and index.
7.1
5-8
1150L
Keywords: African Americans -- Civil rights -- History -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights workers -- United States -- Juvenile literature; African Americans -- Civil rights -- History; Civil rights movements -- History -- 20th century; Civil rights workers